2020
DOI: 10.1108/jsm-01-2019-0037
|View full text |Cite
|
Sign up to set email alerts
|

Witnessing verbal aggression: role of customers’ self-conscious emotions

Abstract: Purpose This paper aims to examine the widespread effects of service actors’ verbal aggression on witness customers’ intentions toward the service organizations through their self-conscious emotions. The moderating roles of the witness customers’ empathic tendencies and the source of aggression are also examined. Design/methodology/approach In two scenario-based experiments and by adopting a multifoci approach, severity of mistreatment (aggression vs incivility vs no-mistreatment) and source of mistreatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 65 publications
0
15
0
Order By: Relevance
“…Third, this study contributes to understanding obese customers’ emotions elicited by weight transformation posts others share on social media. With empirical studies on self-conscious emotion remaining scarce (Bagozzi et al , 2018), more research to examine the distinction between different self-conscious emotions, particularly shame and guilt is needed (Okan and Elmadag, 2020; Parker and Thomas, 2009). Bagozzi et al (2018) highlighted that guilt has been favored in decision-making studies over shame, and more studies are needed to investigate the difference between the two emotions relating to customer behavior.…”
Section: Implications Limitations and Directions For Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, this study contributes to understanding obese customers’ emotions elicited by weight transformation posts others share on social media. With empirical studies on self-conscious emotion remaining scarce (Bagozzi et al , 2018), more research to examine the distinction between different self-conscious emotions, particularly shame and guilt is needed (Okan and Elmadag, 2020; Parker and Thomas, 2009). Bagozzi et al (2018) highlighted that guilt has been favored in decision-making studies over shame, and more studies are needed to investigate the difference between the two emotions relating to customer behavior.…”
Section: Implications Limitations and Directions For Future Researchmentioning
confidence: 99%
“…Empirical studies on self-conscious emotion are limited (Bagozzi et al , 2018). Researchers have called for more studies to examine the distinction between different self-conscious emotions, particularly shame and guilt (Okan and Elmadag, 2020; Parker and Thomas, 2009). Decision-making studies have favored guilt over shame when examining customer behavior (Bagozzi et al , 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In this situation, passengers may lose their emotional control and ultimately encourages passengers to distance and lower the relationship quality. Accordingly, it motivates passengers to be involved in aggressive behavior such as avoiding a future relationship with a firm (Okan and Elmadag, 2020).…”
Section: Integraɵonmentioning
confidence: 99%
“…3. While some have questioned the use of MTurk, studies show that MTurk is commonly used (e.g. Karabas et al , 2020; Newton et al , 2018; Okan and Elmadag, 2020) because it provides demographically diverse, cost-effective and quality data (Berinsky et al , 2012; Buhrmester et al , 2011; Kees et al , 2017; Paolacci and Chandler, 2014). We believe the present studies yield reliable findings given that we excluded previous participants in our studies each time we conducted a new study, our samples were fairly representative, manipulation checks showed our scenarios were interpreted as intended, our measures were reliable and our findings replicated across numerous studies.…”
Section: Notesmentioning
confidence: 99%